1975
DOI: 10.1084/jem.141.6.1453
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation between mitogenicity and immunogenicity of TNP- lipopolysaccharide, a T-independent antigen

Abstract: Two models have been proposed to explain triggering of B cells by so-called T-independent antigen. Feldmann and Basten (1) proposed that the interaction of multiple repeating determinants on polymeric antigens with specific Ig receptors on the B-cell surface is sufficient to provide the signals for division of these cells and differentiation to antibody-forming cells. In contrast, coutinho et al. (2, and see review, 3) have claimed that there is only one signal, a mitogenic signal, receptors acting merely as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
27
1

Year Published

1976
1976
1992
1992

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(32 citation statements)
references
References 18 publications
4
27
1
Order By: Relevance
“…Similar dissociations of the properties of LPS have been demonstrated after interaction with the cyclic peptide antibiotic, polymyxin B, in vitro (37,(40)(41)(42)(43)(44)(45). Polymyxin B-treated LPS, though no longer mitogenic (37) nor anticomplementary (45), still retains its ability to generate an immune response when complexed with a hapten (37).…”
mentioning
confidence: 54%
See 2 more Smart Citations
“…Similar dissociations of the properties of LPS have been demonstrated after interaction with the cyclic peptide antibiotic, polymyxin B, in vitro (37,(40)(41)(42)(43)(44)(45). Polymyxin B-treated LPS, though no longer mitogenic (37) nor anticomplementary (45), still retains its ability to generate an immune response when complexed with a hapten (37).…”
mentioning
confidence: 54%
“…Polymyxin B is bactericidal for most Gram-negative bacteria, and it has been reported to prevent the lethal endotoxin activity of LPS (40)(41)(42)(43)(44) as well as to alter the physical structure of LPS (37,45 myxin B (Fig. 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings, summarized in Table III, indicate that the two responses represent separate pathways of B-cell activation by LPS, one representing direct interaction between LPS and B cells (mitosis), the other depending on macrophages or macrophage-produced factors (antigendependent production of antibody). A dissociation between the adjuvant activity of LPS and its mitogenic effect on B cells has also been suggested by Jacobs and Morrison (22) who reported that the cationic polypeptide antibiotic, polymyxin B, abrogates the mitogenic effect of LPS but enhances the immune response to TNP conjugated with LPS.…”
Section: Responder Macrophages Support the Lps-induced Production Of mentioning
confidence: 91%
“…From these results, we have made an assumption that the same molar amounts of lipid A of each LPS fraction should have the same effect on splenocyte mitogenesis. Mitogen assay was carried out as previously described (14). The result is shown in Fig.…”
mentioning
confidence: 99%